Numerical analysis of the stress shadowing effects in multistage hydrofracturing - SONG Jinxin; YU Hang; WANG Yating; CHEN Jialiang; JU Yang (矿业科学学报, 2024)
Multistage fracturing is a commonly-used method to improve gas production in tight hydrocarbon reservoirs. Stress shadowing effect among multi-fractures is crucial in effectively connecting the pre-existing natural fracture of reservoir and forming a complex fracture network that facilitates gas flow. Challenges remain in accurately characterizing the fracture structure and propogation patterns of naturally fractured reservoirs. In this study, we adopt an adaptive finite-discrete element method to simulate the multistage fracturing of a naturally fractured reservoir by improving the mesh auto-refinement and identification of multiple fracture propagation. The numerical model covers interactions among hydraulic fractures, pre-existing fractures, and microscale pores, while integrates the nonlinear Carter leak-off criterion to describe fluid leak-off and hydromechanical coupling effects during multistage fracturing. We introduce the proppant transport equation for idealised parallel plate flow in fractures, and Darcy's law is adopted to analyse the seepage flow in the fracture network and determine gas recovery. We then compare the fracture network and consequent fluid flow induced by the hydrofracturing of unfractured and naturally fractured models to assess the influence of pre-existing fractures on multistage fracturing behaviour and gas production. This study provides a new approach to determine and optimize fracturing cluster spacing in tight gas reservoirs.